Formal act of defection from the Catholic Church: Canon 1086, §1 - Herranz Casado, Julián (Roman Replies and CLSA Advisory Opinions 2006, 2006)
His Eminence, Julian Cardinal Herranz, President of the Pontifical Council on Legislative Texts, sent a letter to the Presidents of all Episcopal Conferences concerning the elements necessary for an act of formal defection from the faith. This has important practical consequences for those who must determine whether a person who has formally defected from the Church is bound by the impediment of disparity of cult (c. 1086 § 1), must observe the canonical from marriage (c. 1177), or deeds permission to enter a marriage with baptized non -Catholic (c. 1124). This letter was approved by the Supreme Pontiff, Benedict XVI, who directed that it be transmitted to all Presidents of Episcopal Conferences."